Microvascular decompression: Diversified of imaging uses, advantages of treating trigeminal neuralgia and improvement after the application of endoscopic technology - Yu, Gui; Leng, Jingxing; Xia, Yinghua; Min, Feixiang; Xiang, Hui (Frontiers in Neurology, 2022)
Classical trigeminal neuralgia (CTN) is a unilateral and severe facial pain disease, which seriously affects the patient's quality of life. Microvascular decompression (MVD) is currently the most effective surgical method, and it is the only treatment for the etiology of CTN. Imaging for MVD has been increasingly used, and the advantages and disadvantages of endoscopy-assisted vascular decompression surgery have been controversially debated. In this review, we aimed to discuss the advantages of MVD in the treatment of patients with CTN, the importance of using imaging in disease management, and the improvements of vascular decompression surgery through the application and maturity of endoscopic techniques. Compared with other surgical methods, MVD has more prominent short- and long-term treatment effects. Its selection depends on the accurate discovery of neurovascular compression by preoperative imaging. Moreover, magnetic resonance imaging plays a diverse role in MVD, not only in identifying the responsible vessels but also in determining the prognosis and as a tool for scientific research. The use of endoscopic techniques provides improved visualization of the MVD and additional benefits for vascular decompression surgery.